MENINGKATKAN HASIL BELAJAR BIOLOGI PADA MATERI KONSEP KROMOSON DAN GEN DNA DENGAN MENGGUNAKAN METODE PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH PADA SISWA KELAS XII SMA NEGERI 9 PEKANBARU - Irna Suryanti (JURNAL PAJAR (Pendidikan dan Pengajaran), 2017)
This research is motivated by the lack of learning outcomes biology class XII at SMA Negeri 9 Pekanbaru. This study aims to improve the learning outcomes of biology in studying material concept chromosomes and DNA genes class XII at SMA Negeri 9 Pekanbaru use of cooperative learning method types make a match. The subjects were all class XII students of SMA Negeri 9 Pekanbaru totaling 30 people, in the academic year 2016-2017. Form of research is classroom action research. The research instrument consists of instruments and instrument performance data collection activity observation sheet form teacher and student activity. Based on the observation of the first symptoms of student learning outcomes gained an average of 52.3 medium category with classical completeness 30%. Then based on achievement test results in the first cycle which indicates that the level of student learning outcomes achieved an average of 61.7 medium category with classical completeness 53%. While on the second cycle increased achieve the learning outcomes of students gained an average of 73 including both categories with classical completeness 90%. This success is due to implement cooperative learning make a match, student activities to become more active, which means students tend to be positive in the learning process given by the teacher. Under these conditions, the enrollment rate will increase and in turn can improve student learning outcomes.